Academic enrepreneurship and organisational support factors - Urban, B.; Gamata, S. (South African Journal of Higher Education, 2020)
Academic entrepreneurship has gained popularity in recent decades as an important feature in the movement towards a knowledge society. Research shows that the organisational context can facilitate or impede academic entrepreneurship. However academics are often faced with a weak set of institutional and organisational factors which inhibit the commercialisation and technology innovation process. This article builds in the direction of this emerging stream of research and empirically investigates the relationship between the management support, rewards and incentives, time allocation and measurable academic entrepreneurship outputs. Following a survey of universities and research councils in South Africa, the results reveal several positive interrelationships between the study variables. In particular rewards were found to have a significant impact on academic entrepreneurship outputs. Implications relate to management interventions to design and implement simple and harmonised academic entrepreneurship support mechanisms which focus on rewards and incentives.